Essentials of Biotechnology - R.C. Sobti (Ane Books Pvt. Ltd, 2009)
"A comprehensive treatise on biotechnology, this volume starts with an overall review of early applications that scientists employed long before the field was defined. It then moves on to examine the emergence of current methods and specialized tools in the field, as well as cell culture and nucleic acid based technologies. It devotes individual chapters to biotechnology in the areas of health, agriculture, environment, aquaculture, and food. These are followed by chapters on the status of biotechnology in developing countries with special reference to India. It also discusses debated ethical considerations and explores ongoing issues regarding intellectual property rights and patents."--Publisher's website.